Economic and competence regions: a descriptive analysis of Danish regions - Mette Praest Knudsen (European Regional Science Association (ERSA), 2002)
The prosperity of the capital city and surrounding area has been used as one fundamental argument for localisation of large foreign companies. But recent research on regional systems of innovation has emphasised, not just the structure of the system, like strong educational institutions, better transportation systems and access to political actors, but also the local knowledge base as determinants. Today, the structural factors are less important in part because of ICT, but also because policy initiatives have become embedded in the local political system, whereas the local knowledge base and access to highly specialised personnel like engineers (Dalum et al., 1999) are strongly emphasised. The success factors of a region has been narrowed down to eight (Isaksen (1998) and Voyer (1998)): specialisation within one or more industries; the role of local networks; availability of R&D and educational institutions; access to a qualified work force; access to competent financial institutions; cooperation between firms and other institutions; contacts to knowledgeable milieus elsewhere and a high degree of innovativeness (differences are seen between Isaksen and Voyer, these eight are based on Isaksen (op. cit. page 15-21). The aim of this paper is to explore some of the above mentioned success characteristics for the 14 counties ('aemter') in Denmark to discuss whether the main economic region in Denmark is also the competence region, and to what extent it is successful. The paper tries to assess to what extent the financial strengths or weaknesses reflect the innovation capacity of the region and how the relationship evolves over time. Furthermore, the paper attempts to identify the main drivers of growth within the regional system of innovation. Hence, does the capital region (Copenhagen and surroundings) of Denmark encompass better conditions in terms of the local knowledge base, the scientific and technical potential and the availability of trained personnel than the Western part of Denmark (incl. Funen and Jutland) for the development of knowledge intensive clusters. A discussion of the terms economic and competence region is given in the paper and indicators are applied. The local knowledge base is in particular thought of as the technological and scientific knowledge, which are proxied by patents, bibliometrics and educational data. The dual nature of knowledge production is stressed in the discussion of the regions. On the one hand, the firm localises in areas of complementary knowledge assets within the same industry, but benefits can accrue to a region from the activities of firms in that region (Voyer 1998: 81) as well. Furthermore, the role of universities and research institutes is important in two respects, first as sources of significant innovation-generating knowledge (Acs et al. 1998: 112), and second as educators of future employees of the firms in the region (for empirical tests see Almeida (1999)). To address these issues, the paper presents indicators of the science potential, the availability of personnel as well as the density of scientific and technical personnel. Finally, the role of local policy makers is discussed in two short case studies in the final part of the paper. From the descriptive parts the paper moves on to test whether the above variables are determinants of value added (economic growth), technological specialisation (strong local knowledge base) and international ...?
Keywords: 330